Motivation Mediate the Effect of Education, Work Experience, Intellectual Intelligence, and Discipline on Employee Performance - Wayan Gede Endra Bratha; Ni Nyoman Sawitri; Dewi Puspaningtyas Faeni (Journal of Accounting and Finance Management, 2023)
The purpose of this study is to analyze the effect of education, work experience, intellectual intelligence and work discipline on employee performance mediated by motivation at the Directorate of Security for Vital Objects of the National Police. The population is 170 respondents using saturated sample technique. Data analysis technique using SEM-PLS. The results of the analysis show that education has a positive and significant effect on employee performance, experience has a positive and significant effect on employee performance, intellectual intelligence has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, education has a positive but not significant effect on motivation, work experience has a positive but not significant effect on motivation, intellectual intelligence has a positive and significant effect on motivation, work discipline has a positive but not significant effect on motivation, motivation has a positive and significant effect on employee performance, motivation is unable to mediate the effect of education on employee performance, motivation unable to mediate the effect of experience on employee performance, motivation is able to mediate the effect of intellectual intelligence on employee performance and motivation is able to mediate the effect of discipline k work on employee performance.